Nursing Strategies on the Prevention of Ocular Complications Among Patients with Altered Level of Consciousness - Vijayaraj; Seethalakshmi, A.; Porkodi, A. (Journal of Health and Allied Sciences NU, 2017)
Background: Ocular trauma is the cause of blindness in more than half a million people worldwide. A lack of attention to the eye or poor eye care can lead to cross infection and may cause damage to the eye. This investigation aimed to determine the effectiveness of nursing strategies on prevention of ocular complications among patients with altered level of consciousness (GCS <8) and associate the occurrence of ocular complications with clinical variables.Method: The research design adopted for this study was true experimental. A pilot study was initially under taken. Eight samples, four in each group were selected. The main study was conducted for over a period of 4 weeks. A total of 40 samples were selected, 20 in each group. Ocular complication assessment scale developed by the author was used to assess the effectiveness of nursing strategies on prevention of ocular complication.Results: There was a significant difference in the ocular complication prevention in the study group patients who received planned sequential eye care as compared to that of the control group patients who received the routine eye care.Discussion: Increasing the frequency of eye care Q4th hourly from routine eye care was found to be effective in reducing the ocular complications among the patients with altered level of consciousness.
Keywords: altered level of consciousness (GCS <8); Nursing Strategies; eye care protocol; samples; Q4th hourly; Eye care